Peripheral FGFR1 Regulates Myofascial Pain in Rats via the PI3K/AKT Pathway - Zhang, Mingyang; Jin, Feihong; Zhu, Yuchang; Qi, Feng (Neuroscience, 2020)
•P-FGFR1 is upregulated in the patients with myofascial trigger points.•FGF2 activate FGFR1 in the nerves around myofascial trigger points in rats.•The expression of p-FGFR1 in DRG of MTrPs group is higher than control group.•Intramuscular injection of FGFR1 and PI3K inhibitors alleviate myofascial pain in rats. Myofascial pain syndrome (MPS) is a type of skeletal pain identified by myofascial trigger points (MTrPs). The formation of MTrPs is linked to muscle damage. The fibroblast growth factor receptor (FGFR1) has been found to cause pain sensitivity while repairing tissue damage. The aim of the current study was to explore the mechanism of FGFR1 in MTrPs. We used a RayBio human phosphorylation array kit to measure p-FGFR1 levels in human control subjects and patients with MTrPs. P-FGFR1 was upregulated in the patients with MTrPs. Then a rat model of MPS was established by a blunt strike on the left gastrocnemius muscles (GM) and eccentric-exercise for 8 weeks with 4 weeks of recovery. After establishing the MPS model, the morphology of the GM changed, and the differently augmented sizes of round fibers (contracture knots) in the transverse section and fusiform shapes in the longitudinal section were clearly seen in the rats with myofascial pain. The expression of p-FGFR1 was upregulated on the peripheral nerves and dorsal root ganglion neurons in the MTrPs group. The spinal Fos protein expression was increased in the MTrPs group. Additionally, the mechanical pain threshold was reduced, and the expression of FGF2, p-FGFR1, PI3K-p110γ, and p-AKT increased in the MTrPs group. PD173074 increased the mechanical pain threshold of the MTrPs group, and inhibited the expression of p-FGFR1, PI3K-p110γ, and p-AKT. Moreover, LY294002 increased the mechanical pain threshold of the MTrPs group. These findings suggest that FGFR1 may regulate myofascial pain in rats through the PI3K/AKT pathway.